Evaluation of quality of life, depression, anxiety and stress among caregivers of people with or without Down Syndrome: a cross-sectional study (Research, Society and Development, 2020)
The act of caring, being responsible for the survival and quality of life of others, represent extra activities that can cause socio-emotional changes to those who perform this function. Objective: To assess the quality of life, depression, anxiety and stress of caregivers of people with or without Down syndrome. Methodology: 144 caregivers were divided into Control Group (caregivers of typical children) and Down Syndrome Group (caregivers of people with Down Syndrome). The controlled observational cross-sectional study was prepared in accordance with the Declaration of Helsinki and approved by the Human Ethics Committee. To achieve the objectives, validated questionnaires related to the theme were applied. The data were subjected to the Chi-square test with modified Bonferroni post hoc and Rank or Pearson correlation tests. Results: The Down Syndrome Group had a lower quality of life related to the psychological domain and a higher environmental domain than the Control Group. In the groups studied, quality of life and family income showed a positive correlation (p = 0.02) and there was no difference in depression. The Control Group had a higher rate of anxiety and the Down Syndrome Group had a higher rate of physical symptoms of stress; correlated with the degree of dependence of the Down Syndrome patient (p = 0.04). Conclusion: Family income is an important factor for a better quality of life, symptoms of physical stress reduce the quality of life in the psychological domain and symptoms of physical stress of caregivers are correlated with a greater degree of dependence of patients with Down Syndrome.